Determination of age-specific and sex-specific familial risks for the different manifestations of venous thromboembolism: A nationwide family study in Sweden - Zöller, Bengt; Li, Xinjun; Sundquist, Jan; Sundquist, Kristina (Thrombosis and Haemostasis, 2011)
This nationwide study aimed to determine whether differences exist in age-specific and sex-specific familial risks for pulmonary embolism (PE), venous thrombosis of the lower limbs (VT) and other forms of venous thromboembolism (OVTE) among offspring, siblings and spouses of affected individuals. The Swedish Multi-Generation Register was linked to the Hospital Discharge Register data for the period 1987–2007. Standardised incidence ratios (SIRs) were calculated for individuals whose relatives were hospitalised for venous thromboembolism (VTE), as determined by the International Classification of Diseases (ICD), and those whose relatives were unaffected by VTE. The total number of hospitalised VTE patients was 45,362. All VTE patients were categorised as PE, VT or OVTE according to ICD at first hospitalisation. For example, the parental SIRs for PE, VT and OVTE in offspring at age 10–19 years were 2.89 (95% CI 1.48–5.06), 4.99 (95% CI 3.22–6.10) and 3.89 (95% CI 2.51–5.75), respectively. The low spousal risks of PE (1.08; 95% CI 1.02–1.13), VT (1.06; 95% CI 1.011.12) and OVTE (1.07; 95% CI 1.00–1.15) suggest the familial risks to be largely genetic. In both men and women, familial relative risks were increased for all the different manifestations of VTE with the exception of those older than 70 years. Familial history is a risk indicator in both sexes, and is potentially useful for clinical risk assessment for the different manifestations of VTE.
Keywords: Venous thrombosis; epidemiology; pulmonary embolism; risk factors; familial thrombosis